STATE BUDGET AS THE LEADING LINK OF THE FINANCIAL SYSTEM OF THE STATE - Ichshanova , R.K. (Academic Journal of Physical and Chemical Sciences, 2018)
It is common knowledge that the efficiency and effectiveness of the state's functions are largely dependent on the construction of an appropriate public financial management system. One of the main tasks of public finance management is to contribute to the sustainable and efficient economic development of the country through the optimization of intergovernmental fiscal relations. In the Republic of Kazakhstan, a cooperative model of inter-budgetary relations was adopted, characterized by the existence of own and regulated taxes for each level of the budget system, increased responsibility of the center for the state of local budgets and an allowable-justified restriction on the actual independence of local authorities in matters of external borrowing. Also, a developed mechanism for the redistribution of financial resources between the levels of the budget system through transfers.